Safety Analysis of Simultaneous Vaccination of Japanese Encephalitis Attenuated Live Vaccine and Measles, Mumps, and Rubella Combined Attenuated Live Vaccine from 2020 to 2023 in Guangzhou, China - Jie Liu; Yong Huang; Fengrui Jing; Yan Kang; Qiaojuan Liu; Zhiwei Zheng; Chunhuan Zhang; Xiaofeng Liang; Zhoubin Zhang (Vaccines)
Objectives: Our objectives were to evaluate the safety of the simultaneous vaccination of Japanese encephalitis attenuated live vaccine (JEV-L) and measles, mumps, and rubella combined attenuated live vaccine (MMR) in children and to provide a reference for the implementation of the strategy of simultaneous vaccination with the two vaccines. Methods: The data of adverse events following immunization (AEFI) and vaccination for JEV-L and MMR from 2020 to 2023 were extracted through the Guangdong Province Vaccine Distribution and Vaccination Management Information System and the Chinese National AEFI Information System (CNAEFIS). The inclusion criteria were that children were born after 1 October 2019, and received the first dose of JEV-L or MMR after 1 June 2020, in accordance with the starting age for vaccination (8 months). The study used the number of vaccine doses as the denominator to calculate and compare the reporting rates of cases and calculated the relative risk (RR) of adverse reactions and the 95% confidence interval (CI). Results: In Guangzhou, a total of 214,238 doses of JEV-L were administered to children. JEV-L and MMR were co-administered in 464,009 doses, and MMR was administered separately in 241,150 doses. The overall reporting incidence rates of AEFI (per 100,000 doses) for JEV-L, the simultaneous vaccination group, and MMR were 11.20, 53.02, and 60.96, respectively. Among children aged 8 months in Guangzhou, 57.98% (463,512/799,423) received the simultaneous administration of JEV-L and MMR. In the reported AEFI events, general reactions accounted for 87.50% in the JEV-L group, 88.21% in the simultaneous vaccination group, and 89.80% in the MMR separate group. The incidence rates of common adverse reactions were 9.80, 46.7, and 54.74, respectively. The incidence rates of rare adverse reactions were 0.93, 3.88, and 2.90, respectively. The reporting incidence rates of fever ≥38.6 °C after vaccination were 4.20, 16.16, and 17.83 for the JEV-L separate group, simultaneous vaccination group, and MMR separate group, respectively. There was a significant difference between the simultaneous vaccination group and the JEV-L separate group (RR = 3.848, 95% CI = 1.927, 7.683), while no significant difference was found compared with the MMR separate group (RR = 0.906, 95% CI = 0.623, 1.318). The simultaneous vaccination group showed no significant differences in the reporting incidence rates of local redness and induration compared with the two separate vaccination groups (RR = 1.385, 95% CI = 0.144, 13.315; RR = 0.390, 95% CI = 0.087, 1.743; RR = 0.520, 95% CI = 0.033, 8.314). No significant differences were found in the incidence rates of rare adverse reactions such as maculopapular rash, urticaria, and thrombocytopenic purpura. Conclusions: The AEFI reporting incidence rate for the first dose of the simultaneous vaccination of JEV-L and MMR in 8-month-old children in Guangzhou is between the rates of the two separate groups. Compared with the MMR separate group, the simultaneous vaccination group does not increase the risk of adverse reactions.